Two sides of the same coin?: What neural processing of emotion and rewards can tell us about complex post-traumatic stress disorder and borderline personality disorder - Rheude, Christiane; Nikendei, Christoph; Stopyra, Marion A.; Bendszus, Martin; Krämer, Bernd; Gruber, Oliver; Friederich, Hans-Christoph; Simon, Joe J. (Journal of affective disorders, 2025)
Background - Borderline personality disorder (BPD) and complex posttraumatic stress disorder (cPTSD) share clinical similarities, complicating diagnosis and treatment. Research on the neurobiology of BPD and monotraumatic PTSD has shown that a prefrontal-limbic imbalance in emotional and reward processing is a hallmark of both disorders, but studies examining this network in cPTSD are lacking. Therefore, this study aimed to directly compare neural processing of emotion and reward during decision making in cPTSD and BPD. - Methods - Using functional magnetic resonance imaging, we measured neural activity in female patients (27 patients with cPTSD, 21 patients with BPD and 37 healthy controls) during a Desire-Reason Dilemma task featuring distracting fearful facial expressions. - Results - We found no differences in neural activation when comparing cPTSD and BPD. However, when grouping patients based on symptom severity instead on diagnosis, we found that increased symptoms of cPTSD were associated with increased activation of dorsolateral prefrontal cortex during reward rejection, whereas increased symptoms of BPD were associated with decreased activation in prefrontal and limbic regions during reward rejection with distracting negative emotional stimuli. - Conclusion - This is the first study to investigate and compare emotional processing and reward-based decision making in cPTSD and BPD. Although we found no neural differences between disorders, we identified symptom-related neural patterns. Specifically, we found that elevated cPTSD symptoms were related to greater sensitivity to reward stimuli, whereas heightened BPD symptoms were related to increased susceptibility to emotional stimuli during goal-directed decision making. These findings enhance our understanding of neural pathomechanisms in trauma-related disorders.